Pathways to HIV testing and care by black African and white patients in London. Issue 1 (1st February 2002) - Erwin, J; Morgan, M; Britten, N; Gray, K; Peters, B
Abstract : Objective: To examine factors associated with uptake of HIV clinic services by black African HIV positive people living in London. Design: Questionnaire survey of patients attending study clinic. Setting: HIV outpatient clinic in south London, UK. Subjects: All HIV positive patients attending the clinic between July 1999 and March 2000. Main outcome measures: Use of health services, delay in seeking HIV test, pre-HIV test concerns, delay in uptake of HIV care, barriers to clinic use, disclosure, sources of support. Results: 392 questionnaires were completed. Respondents were 64% white, 26% black African, and 10% from other ethnic groups. Twenty eight per cent of black Africans suspected they were HIV positive before diagnosis (white patients 45% (p<0.01)). Before testing 11% of black Africans had previously attended a genitourinary medicine clinic, 80% had consulted a GP. Twenty per cent of black Africans expressed concern over entitlement to care and where to get an HIV test. The majority of black Africans (66%) received HIV care within 1 month of their diagnosis. They were significantly (p<0.01) less likely than white patients to disclose their HIV status to family and friends. Conclusion: This study suggests that although black Africans are a high risk group for HIV infection they generally do not suspect their status. While they may delay testing, their uptake of HIV clinic care and use of statutory and voluntary support services after diagnosis is similar to their white counterparts. However, they lack informal support networks. This study highlights the continuing need for health promotion work among London's African communities, to reduce the stigma surrounding HIV/AIDS and to raise awareness of the benefits of testing.